High prevalence of the IVS 1 + 1 G to A/GJB2 mutation among Czech hearing impaired patients with monoallelic mutation in the coding region of GJB2 - Seeman, P; Sakmaryová, I (Clinical genetics, 2006)
Biallelic pathogenic GJB2 gene mutations cause pre-lingual genetic hearing loss in up to 50% of individuals with bilateral sensorineural hearing loss worldwide. Sequencing of the entire GJB2 gene-coding region in Czech patients with pre-lingual bilateral hearing loss revealed that 10.3% of Czech patients carry only one monoallelic pathogenic mutation in the coding region of the GJB2 gene, which is significantly more than the population frequency of 3.4%. The 309-kb GJB6 deletion, frequent in Spain and France, is very rare in the Czech population. In order to evaluate the impact of the IVS1 + 1 G to A splice site mutation in the non-coding part of the GJB2 gene among Czech patients, we tested all available patients with pre-lingual hearing loss with only one monoallelic mutation in the coding part of GJB2. By sequencing of the exon 1 region of the GJB2 gene and HphI restriction analysis in 20 Czech patients we identified nine patients carrying IVS1 + 1 G to A. Testing for this mutation explained deafness in 45% of Czech GJB2 monoallelic patients. This mutation represents now 4% of GJB2 pathogenic mutations in Czech patients and is the third most common GJB2 mutation found in our cohort of 242 unrelated Czech patients with prelingual hearing loss. A similar frequency may also be expected in other Central European or Slavic populations.
Keywords: Hearing Loss, Bilateral; alely; genetické testování; konexiny; Alleles; oboustranná nedoslýchavost; Cohort Studies; Česká republika; DNA Mutational Analysis; konexin 26; mutace; Connexin 26; mutační analýza DNA; Czech Republic; kohortové studie; restrikční mapování; místa sestřihu RNA; Mutation; Humans; Restriction Mapping; Connexins; Genetic Testing; RNA Splice Sites; lidé